UNIT 29.10 Tetra Detector Analysis of Membrane Proteins. (1st August 2014) - Miercke, Larry J.W.; Robbins, Rebecca A.; Stroud, Robert M.
Abstract: Well‐characterized membrane protein detergent complexes (PDC) that are pure, homogenous, and stable, with minimized excess detergent micelles, are essential for functional assays and crystallization studies. Procedural steps to measure the mass, size, shape, homogeneity, and molecular composition of PDCs and their host detergent micelles using size‐exclusion chromatography (SEC) with a Viscotek Tetra Detector Array (TDA; absorbance, refractive index, light scattering, and viscosity detectors) are presented in this unit. The value of starting with a quality PDC sample, the precision and accuracy of the results, and the use of a digital benchtop refractometer are emphasized. An alternate and simplified purification and characterization approach using SEC with dual absorbance and refractive index detectors to optimize detergent and lipid concentration while measuring the PDC homogeneity is also described. Applications relative to purification and characterization goals are illustrated as well. Curr. Protoc. Protein Sci . 77:29.10.1‐29.10.30. © 2014 by John Wiley & Sons, Inc.